Evaluating gifted students’ perceptions of the characteristics of their effective teachers - Aboud, Yusra Zaki (Frontiers in Education, 2023)
This study sought to evaluate how gifted students perceived effective teachers. The study involved 120 teachers from Saudi Arabia, Bahrain, and the United Arab Emirates along with 300 gifted students, both males (n = 144) and females (n = 156). Gifted students responded to three open-ended questions while teachers filled out a background questionnaire. Fewer teachers reported having a major in gifted education than those who said they had a major in education. Additionally, the majority of teachers did not enroll in any courses on gifted education. The three open-ended questions responses showed gifted students valued personal characteristics more highly than professional ones. These results imply that teachers who are adept at working with gifted students should pursue further training.